When Someone You Love is Murdered: A Qualitative Study on the Experience of Families Bereaved by Homicide - Galea-Bateman, Donna (2017)
Homicide is defined as ‘the wilful killing of one human being by another’ (Morales, 1995). After a homicide, family members not only have to cope with their loss and how their loved one died but also with an aftermath of events and consequences that follow. Research suggests this population group to be largely unrecognised as ‘co-victims’ and to feel unsupported by society. Through the lens of qualitative research and Interpretative Phenomenological Analysis, interviews to explore the lived experience of 3 family members bereaved by homicide were analysed. One Superordinate theme (Fig. 1) entitled ‘Bubble’ and three subordinate themes were identified: (1) Sense of Isolation, (2) Sense of Injustice and (3) Sense of Unreality. A secondary Superordinate theme (Fig. 2) of ‘Posttraumatic Growth’ affirms the importance of social support throughout the experience of the unique trauma of homicide towards posttraumatic growth and is further explained (Fig. 3). Recommendations are made for qualitative studies to explore the experience of posttraumatic growth following bereavement by homicide.